The wisdom of the Christian faith - Moser, Paul K., 1957-; McFall, Michael T., 1978- (Cambridge University Press, 2012)
"Although typically separated, philosophy and New Testament theology are mutually beneficial for the understanding of the distinctive wisdom that guides Christian thought and life. The Wisdom of the Christian Faith fills a major gap in the literature on the philosophy of religion. It is the first book on the philosophy of religion to be authored entirely by philosophers while directly engaging themes of wisdom in the Christian tradition. The book consists of all new essays, with contributions from John Cottingham, Paul Gooch, Gordon Graham, John Hare, Michael T. McFall, Paul K. Moser, Andrew Pinsent, Robert Roberts, Charles Taliaferro, William Wainwright, Jerry Walls, Sylvia Walsh, Paul Weithman, and Merold Westphal"--